Maximizing Packet Transmission Opportunities in The Wireless Network by Using The Game Theory - Nguyen , Chánh Tín; Phan , Văn Ca (Journal of Technical Education Science, 2018)
In this paper, the authors have developed a game theory framework for an opportunity communication strategy for wireless networks that operate in a strict energy-constrained environment. In order to minimize unsuccessful transmission due to channel errors and packet collisions that causing a waste of energy, the opportunity communication strategy attempts to transmit at good channel conditions while meeting the delay constraint under the time-varying wireless channel. Thus a constrained cost-coupled stochastic game algorithm is formulated to obtain an optimal threshold for successful transmission in the opportunistic transmission manner. The simulation result shows that with the opportunity transmission strategy, the nodes trend to defer their transmissions in bad channel conditions to avoid collision and reduce packet loss rate. This can lead to improve the performance of energy usage at each node as well as to prolong the network lifetime.